Tax Competition and Tax Harmonisation in an Urban Context - Oana Secrieru (Machidon) (Queen's University, Department of Economics, 2001)
It is a standard prediction in the literature on tax competition that mobility of factors between jurisdictions causes local governments to choose too low tax rates and to underprovide public goods. This paper shows circumstances when the prediction may be false. The prediction may be false when workers live in one jurisdiction and commute to work in another. We show that in an urban setting land developers will make inefficient choices of both tax rates and public expenditures. Whether these are too high or too low from a social point of view is ambiguous. The only unambiguous prediction is that the non-cooperative payroll tax is inefficiently low. In our framework, the locational inefficiency is twofold, both residents and workers are inefficiently allocated across communities in equilibrium. We also show that tax harmonisation and/or voluntary inter-community transfers are not effective in restoring efficiency.
Keywords: H21; H41; H79; R23; R31; 330; Urban; Tax Competition; Tax Harmonisation; Public Goods; Property Tax; Payroll Tax